ABOUT THE SPEED OF WORK OF THE HUMAN BRAIN (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article deals with the study of the human brain, how the system of the humanbrain works, its performance, how the performance is measured. The system of measurement andthe unit of measurement in other objects and other systems are given. The analysis of the controlprocess is carried out, depending on the object or process, on the basis of which, on the basis ofthe information obtained, an algorithm and control software are developed. The temporarydevelopment of the algorithm and control software Ta, Ta is determined less than the control timeTcon. The algorithms are developed in a real-time system.